2019
DOI: 10.1016/j.biopsych.2018.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Model-Free and Model-Based Influences in Addiction-Related Behaviors

Abstract: Background: Disruptions in the decision-making processes that guide action selection are a core feature of many psychiatric disorders, including addiction. Decision-making is influenced by the goal directed and habitual systems that can be computationally characterized using model-based and model-free reinforcement learning algorithms, respectively. Recent evidence suggests an imbalance in the influence of these reinforcement-learning systems on behavior in substancedependent individuals, but it is unknown if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 33 publications
6
43
0
Order By: Relevance
“…Our finding that lose-shift behavior is decreased in HE rats who had some reversal experience is consistent with findings in rats exposed to methamphetamine [34,35] and in human addicts [66][67][68]. Rats self-administering methamphetamine have also been reported to show impaired learning from unrewarded outcomes, resulting in reduced model-free learning after stimulant treatment [34] and after non-contingent methamphetamine administration [35]. In addition, model-based impairments have been reported in rats during reversal [34] and habitual behavior on reinforced learning tasks has been reported in humans [67].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding that lose-shift behavior is decreased in HE rats who had some reversal experience is consistent with findings in rats exposed to methamphetamine [34,35] and in human addicts [66][67][68]. Rats self-administering methamphetamine have also been reported to show impaired learning from unrewarded outcomes, resulting in reduced model-free learning after stimulant treatment [34] and after non-contingent methamphetamine administration [35]. In addition, model-based impairments have been reported in rats during reversal [34] and habitual behavior on reinforced learning tasks has been reported in humans [67].…”
Section: Discussionsupporting
confidence: 91%
“…An important objective of this research was to investigate the nature of the widely reported impairing effects of cocaine on the flexibility of goal-directed behavior [17,28,[62][63][64][65]. Our finding that lose-shift behavior is decreased in HE rats who had some reversal experience is consistent with findings in rats exposed to methamphetamine [34,35] and in human addicts [66][67][68]. Rats self-administering methamphetamine have also been reported to show impaired learning from unrewarded outcomes, resulting in reduced model-free learning after stimulant treatment [34] and after non-contingent methamphetamine administration [35].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Addiction to alcohol and other drugs is characterized by a shift from decision‐making based on representations of outcome value (goal‐directed or “model‐based” reward‐seeking) toward stimulus‐evoked reward‐seeking based on either the incentive motivational properties of cues (Robinson & Berridge, ), the development of habits (Everitt & Robbins, ; Vandaele & Janak, ), or “model‐free” reward‐seeking (Lucantonio, Caprioli, & Schoenbaum, ; Reiter, Deserno, Wilbertz, Heinze, & Schlagenhauf, ; Sebold et al., ; but see Groman, Massi, Mathias, Lee, & Taylor, ). These shifts in decision‐making can be driven by both associative and non‐associative drug exposure.…”
Section: Introductionmentioning
confidence: 99%